Full-scale testing and modeling of rock-shed shock absorbers under impact loads. Issue 2 (June 2018) - Hsu, Shen Hsiang; Maegawa, Koji; Hama, Akiko
Shock absorbers are often situated on top of rock-sheds to mitigate the effects of geological disasters such as rockfalls. In this study, three full-scale impact load tests, with impact energies of approximately 250, 500, and 1000 kJ, investigated a new type of shock absorber comprising expanded polystyrene, steel material, and sand cushion. Comparing the results of the full-scale tests with the results through sand cushion—a common material used for shock absorbers—the maximum impact load in this study was reduced by around 50% than the empirical formula suggested by a rockfall mitigation code. Besides, the study utilized LS-DYNA finite element software to find out the limitation of energy absorption, accuracy of simulation, input parameters for inferential impact formulas of the shock absorber, and to generate a reasonable simulation for use in further research and design of rock-sheds.